Mismatch Negativity to Acoustic Differences Not Differentiated Behaviorally - Dalebout, Susan D.; Stack, Janet W. (Journal of the American Academy of Audiology, 1999)
Mismatch negativity (MMN) reportedly reflects the neurophysiologic detection of acoustic differences, rather than the phonemic categorization of speech sounds. The purpose of the present study was to determine if it is elicited by speech contrasts that are acoustically different but are not differentiated by listeners in behavioral tasks. Experimental stimuli were drawn from a synthetically generated continuum that varied in place of articulation from /da/ to /ga/. Contrasts used to elicit MMN were (a) the continuum endpoints, (b) the two-step contrast that straddled each listener's categorical boundary, and (c) a within-category contrast that was not behaviorally differentiated by any of the listeners. MMN responses were elicited by all three experimental contrasts. It appears that MMN may be an index of the neurophysiology underlying the ability or inability to discriminate the acoustic parameters necessary for speech perception, rather than a neurophysiologic correlate of behavioral speech discrimination ability. However, limitations involving identification of MMN in the responses of individual listeners confounded this interpretation.Abbreviations: 1–9 contrast = contrast between stimulus continuum endpoints, 7–9 contrast = contrast between steps 7 and 9 on the stimulus continuum, Cz = vertex, F1-F5 = first through fifth formants, Fz = 30 percent of the distance between nasion and inion at the midline, listener MAX = the two-step stimulus contrast that was discriminated best by each listener, MMN = mismatch negativity
Keywords: Auditory evoked potentials; mismatch negativity; P300